Characterization of the phylogenetic diversity of five novel species belonging to the genus Bifidobacterium: Bifidobacterium castoris sp. nov., Bifidobacterium callimiconis sp. nov., Bifidobacterium goeldii sp. nov., Bifidobacterium samirii sp. nov. and Bifidobacterium dolichotidis sp. nov. Issue 5 (21st February 2019) - Duranti, Sabrina; Lugli, Gabriele Andrea; Napoli, Stefania; Anzalone, Rosaria; Milani, Christian; Mancabelli, Leonardo; Alessandri, Giulia; Turroni, Francesca; Ossiprandi, Maria Cristina; van Sinderen, Douwe; Ventura, Marco
Abstract : Five Bifidobacterium strains, i.e. 2020B T, 2028B T, 2033B T, 2034B T and 2036B T, were isolated from European beaver ( Castor fiber ), Goeldi's marmoset ( Callimicogoeldii ), black-capped squirrel monkey ( Saimiriboliviensis subsp. peruviensis ) and Patagonian mara ( Dolichotispatagonum ). All of these isolates were shown to be Gram-positive, facultative anaerobic, d -fructose 6-phosphate phosphoketolase-positive, non-motile and non-sporulating. Phylogenetic analyses based on 16S rRNA gene sequences, multilocus sequences (including hsp60, rpoB, dnaJ, dnaG and clpC genes) and the core genome revealed that bifidobacterial strains 2020B T, 2028B T, 2033B T, 2034B T and 2036B T exhibit close phylogenetic relatedness to Bifidobacterium biavatii DSM 23969 T, Bifidobacterium bifidum LMG 11041 T, Bifidobacterium choerinum LMG 10510 T, Bifidobacterium gallicum LMG 11596 T, Bifidobacterium imperatoris LMG 30297 T, Bifidobacterium italicum LMG 30187 T and Bifidobacterium vansinderenii LMG 30126 T, respectively. Further genotyping based on the genome sequence of the isolated strains combined with phenotypic analyses, clearly show that these strains are distinct from each of the type strains of the so far recognized Bifidobacterium species. Thus, Bifidobacterium castoris sp. nov. (2020B T =LMG 30937 T =CCUG 72816 T ), Bifidobacterium callimiconis sp. nov. (2028B T =LMG 30938 T =CCUG 72814 T ), Bifidobacterium samirii sp. nov. (2033B T =LMG 30940 T =CCUG 72817 T ), Bifidobacterium goeldii sp. nov. (2034B T =LMG 30939 T =CCUG 72815 T ) and Bifidobacterium dolichotidis sp. nov. (2036B T =LMG 30941 T =CCUG 72818 T ) are proposed as novel Bifidobacterium species.